Delayed Glucose Peak and Elevated 1-Hour Glucose on the Oral Glucose Tolerance Test Identify Youth with Cystic Fibrosis with Lower Oral Disposition Index - Tommerdahl, Kalie L. (J Cyst Fibros, 2020)
BACKGROUND: Alternate methods for characterizing oral glucose tolerance tests (OGTT) have emerged as superior to the 2-hour glucose in identifying individuals at risk for type 2 diabetes. The significance of these methods in cystic fibrosis (CF) is unclear. We compared 3 OGTT classifications in youth with CF: 1. curve shape (biphasic vs. monophasic), 2. time to glucose peak (≤30minutes vs. >30minutes), 3. 1-hour glucose (1hG) <155mg/dL vs. ≥155mg/dL to traditional OGTT criteria to determine which best identifies lower oral disposition index (oDI), pulmonary function, and body mass index (BMI). METHODS: Youth 10–18 years with CF, not on insulin, underwent 2-hour OGTT. Glucoses were classified by traditional criteria and 3 alternate methods as normal (biphasic curve, glucose peak ≤30minutes, and/or 1hG <155mg/dL) or abnormal (monophasic curve, glucose peak >30minutes, and/or 1hG ≥155mg/dL). oDI was calculated [1/fasting insulin*(ΔInsulin(0–30min)/ΔGlucose(0–30min))]. Mean oDI, BMI, forced expiratory volume in 1 second (FEV1), and forced vital capacity (FVC) were compared by OGTT classification. RESULTS: Fifty-two youth with CF participated (mean±SD age 13±4years; 37% male; BMI z-score 0.0±0.8; FEV1 88±16.3%; FVC 97±14.8%). Late time to peak glucose and 1hG ≥155mg/dL identified individuals with lower oDI (p=0.01); traditional OGTT criteria for prediabetes did not. No OGTT classification identified individuals with worse BMI nor pulmonary function. oDI was not associated with BMI, FEV1, or FVC. CONCLUSIONS: Alternate OGTT measures including time to peak glucose and 1hG better identify oDI abnormalities than traditional criteria. Further studies are required to determine whether these alternate methods identify individuals with CF at risk for future clinical decline.